Electrophysiological functional recovery in a rat model of spinal cord hemisection injury following bone marrow-derived mesenchymal stem cell transplantation under hypothermia★ - Wang, Dong (Neural Regen Res, 2012)
Following successful establishment of a rat model of spinal cord hemisection injury by resecting right spinal cord tissues, bone marrow stem cells were transplanted into the spinal cord lesions via the caudal vein while maintaining rectal temperature at 34 ± 0.5°C for 6 hours (mild hypothermia). Hematoxylin-eosin staining showed that astrocytes gathered around the injury site and formed scars at 4 weeks post-transplantation. Compared with rats transplanted with bone marrow stem cells under normal temperature, rats transplanted with bone marrow stem cells under hypothermia showed increased numbers of proliferating cells (bromodeoxyuridine-positive cells), better recovery of somatosensory-evoked and motor-evoked potentials, greater Basso, Beattie, and Bresnahan locomotor rating scores, and an increased degree of angle in the incline plate test. These findings suggested that hypothermia combined with bone marrow mesenchymal stem cells transplantation effectively promoted electrical conduction and nerve functional repair in a rat model of spinal cord hemisection injury.